Plasma exchange as treatment for acute fatty liver disease of pregnancy. Issue 3 (28th January 2021) - Aabdi, Mohammed; Mellagui, Yassine; Ouachaou, Jamal; Ounci, Essad; Bkiyar, Houssam; Housni, Brahim
Abstract: Acute fatty liver disease of pregnancy AFLP is an obstetrical emergency, with severe complications that may include death. Management of AFLP is challenging and include plasma exchange which helps to improve the prognosis for both mother and fetus and delay liver transplantation. Abstract : Acute fatty liver disease of pregnancy AFLP is an obstetrical emergency, with severe complications that may include death. Management of AFLP is challenging and include plasma exchange which helps to improve the prognosis for both mother and fetus and delay liver transplantation.